Current performance and methods of determining the cost-effectiveness of using them in practice, domestic banks (Journal of Economic Research & Business Administration, 2015)
The article considers the current performance of the organization and cost-benefit analysis method of their implementation in practice of domestic banks. Also described the importance of strategic management accounting in the current market conditions, in particular the performance of strategic management accounting as the balanced scorecard and economic value added. The introduction of these indicators provide a quality analysis of profitability of banks. And this is very important. The purpose of this work - the analysis of profitability by category of economic in aim of it is optimization through the improvement of analyzing profitability. Implementation of the above indicators will improve the quality of the analysis of profitability of banks. the construction of the concept of the future strategic development based on these indicators will help determine the most pravvilnye methods and ways to improve profitability. The article also said that the programs included these indicators more effectively.
Keywords: strategic management accounting; balanced scorecard; economic value added; cost-benefit analysis of the bank